2014
DOI: 10.4102/curationis.v37i1.1146
|View full text |Cite
|
Sign up to set email alerts
|

Challenges encountered by critical care unit managers in the large intensive care units

Abstract: Unit managers in large ICUs face multifaceted challenges which include the demand for efficient and sufficient specialised nurses; lack of or inadequate equipment that goes along with technology in ICU and supplies; and stressors in the ICU that limit the efficiency to plan, organise, lead and control the daily activities in the unit. The challenges identified call for multiple strategies to assist in the efficient management of large ICUs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 12 publications
0
21
0
3
Order By: Relevance
“…It is not only in this study that the participants complained about the lack of equipment, but Matlakala et al (2014:n.p) also found that unit managers agreed that the right equipment was not available and if it was, it would inevitably be of poor quality. Insufficient supplies of equipment are thus proving to be an obstacle related to material resources.…”
Section: Subtheme: Lack Of Equipmentmentioning
confidence: 55%
“…It is not only in this study that the participants complained about the lack of equipment, but Matlakala et al (2014:n.p) also found that unit managers agreed that the right equipment was not available and if it was, it would inevitably be of poor quality. Insufficient supplies of equipment are thus proving to be an obstacle related to material resources.…”
Section: Subtheme: Lack Of Equipmentmentioning
confidence: 55%
“…[56,58] In critical care settings, work complexity at the point of care places greater reliance on bedside nurses to provide mentorship and clinical support to junior colleagues. [22] Front line management, education and clinical support positions must therefore be incrementally increased and aligned to the size of the nursing workforce by modeling the ratio of these resources per each pod of ten to twelve beds. [15] Ensuring visibility, access and interaction with front-line leaders also positively affects the level of personal accomplishment and is a key determinant of nurses' intention to leave.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally for the hot-floor, approximately 13% more nurses intended to resign within 12-months and this was associated with a higher level of reported depersonalisation potentially due to the larger clinical workforce reducing the sense of cohesion. [22,66] Disconnected, or isolated, nurses experience poor collegial communication and increased emotional fatigue that manifests as an unfeeling, impersonal or callous response toward patients, family and colleagues. [23,67,68] Up to 48% of critical care nurses have been found to experience depersonalisation, the subsequent professional and social isolation of which may hinder participation, undermine teamwork and compound burnout.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiences and challenges of caring for critically ill patients in the ICUs have been reported in some studies globally and also in Africa including Nigeria and South Africa [11,12]. In Tanzania, needs of the family of critically ill patients and their satisfaction with care were reported [13].…”
Section: Data Collectionmentioning
confidence: 99%